answersLogoWhite

0


Best Answer

You can use the quadratic formula for an equation of the form a*x^2 + b*x + c = 0.

x = (-b +/- sqrt(b^2-4*a*c))/(2*a)

In this case:

a = 1

b = -3

c = -28

x = (3 +/- sqrt(9 - 4*(-28)))/2

x = (3 +/- sqrt(121))/2

x = (3 +/- 11)/2

x = 7 or -4

Another option is to attempt to simplify the equation into the form (x-a)(x-b) = 0.

Sometimes you can do this by observation.

For example:

28 = 4*7

7-4 = 3

Thus:

(x-7)(x+4)=0

In this case, a and b are known as the "roots" of the equation, with a = 7 and b = -4.

User Avatar

Wiki User

12y ago

Still curious? Ask our experts.

Chat with our AI personalities

DevinDevin
I've poured enough drinks to know that people don't always want advice—they just want to talk.
Chat with Devin
RossRoss
Every question is just a happy little opportunity.
Chat with Ross
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa

Add your answer:

Earn +20 pts
Q: How do you solve x2-3x-28 equals 0?
Write your answer...
Submit
Still have questions?
magnify glass
imp